Kualitas Hidup Pasien Diabetes Melitus Tipe 2 - Harsismanto J; Padila Padila; Juli Andri; Andry Sartika; Muhammad Bagus Andrianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of Diabetes Self Management Education (DSME) on patients' quality of life with type 2 diabetes mellitus by using a pre-experimental design one group pre and post-test with a sample of 15 respondents. The results of the study, most of the respondents, as many as eight people (53.3%) aged 56-70 years, most of them 14 people (93.3%) were women, most of them eight people (53.3%) had junior high school education, most of them were nine people (60.0%) 1-5 years had diabetes, before the DSME the lowest quality of life score was 86. The highest was 99, the average was 90.93, while after DSME, the most inferior quality of life score was 88, and the highest was 105. The average standard is 98.67. The middle grade of life after treatment has increased. The difference in the mean quality of life scores before and after using DSME with p-value = 0.000. In conclusion, there is an effect on the quality of life of type 2 DM patients before and after being given Diabetes Self Management Education (DSME) in the Work Area of ​​the Pasar Ikan Bengkulu Health Center. Keywords: Diabetes Self Management Education (DSME), Quality of Life